Emotional Intelligence and Academic Performance of Students - Rehman, Rehana; Tariq, Sundus; Tariq, Saba (Journal of the Pakistan Medical Association, 2022)
Medical profession deals with human interactions and ability to empathize improves clinical interactions as well as brings out good clinical outcomes. This has led to increasing interest in the importance of Emotional Intelligence (EI) for effective clinical practice. EI integrates the important aspects of interpersonal and intrapersonal relationships to promote self-management skills like adaptability, control of temperaments and tension free states, which have a profound effect on the academic performance of students. There has been substantial evidence proving that being emotionally intelligent can help individuals excel through life transitions starting from school to college, and later into to the working world. There are many studies in the literature that examine the correlation between EI and academic achievement in different education levels which signify importance of EI levels to predict “students who are in need of guided intervention”.